On Democritean Rhysmos - Gomes, Gustavo Laet (Revista Archai, 2019)
In Metaphysics A.4 (985b4-19 [DK67 A6]), Aristotle provides crucial information about fundamental aspects of the chemistry and microphysics of the atomic theory of Leucippus and Democritus of Abdera. Besides the plenum and the void, which he identifies as the elements of the atomic theory, he presents what he himself names as differences. These fundamental differences are named so because they ought to be responsible for the emergence of all other differences in the physical world, and especially the ones that hit our senses. Aristotle provides a list of three differences both in what is recognized as autochthonous terminology from Leucippus and Democritus, and in a translation to terms apparently more intelligible to Aristotelian listeners. Among those differences there is one in particular that is harder to comprehend than the other ones: rhysmos. Aristotle’s translation of rhysmos into schÄ“ma has led most interpreters to acknowledge that it referred solely to atoms individually, while the other two differences would refer to relations between atoms. In this paper, I want to propose an interpretation in which rhysmos actually refers to several aspects of the chemistry and microphysics of the atomic theory.